KEPADATAN POPULASI BEKICOT (Achatina fulica) PADA PERTANAMAN NAGA (Hylocereus costaricensis) DI KANAGARIAN TAPAKIS KECAMATAN ULAKAN TAPAKIS KABUPATEN PADANG PARIAMAN - Putri, Micke Adeva (STKIP PGRI Sumbar, 2014)
Including land snail Achatina fulica, which generally has a humid place habits and activeat night (nocturnal). Nocturnal nature is not solely determined by the dark at night but isdetermined by the temperature and humidity environment factors. These animals eat a variety ofplant cultivation, therefore, the snails including one for crop pests. Part of the plant is attackedyoung shoots, branches, and trunks. This pest bites invite attack fungi or bacteria that cause plantsto wilt and die.This study aimed to determine the population density at planting dragon Achatinafulica at Kanagarian Tapakis Ulakan Tapakis District of Padang Pariaman. This study wasconducted in May-June 2014 with a descriptive survey method by calculating directly Achatinafulica were obtained at the study site. Sampling was performed by the method mapped 10mx10mon horticultural dragon. Environmental factors were measured at the time of sampling aretemperature and humidity. sampling performed three times in the dark and the bright moon. Basedon the results research conducted on the plant dragon at Kanagarian Tapakis District of PadangPariaman Ulakan Tapakis found the number of individuals Achatina fulica as 3436 individualswith a total population density of 2.29 individuals/ m2, the state optimum temperature at 27 Â° C.